2020
DOI: 10.21203/rs.3.rs-52907/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel and traditional anthropometric indices for identifying metabolic syndrome in non-overweight/obese adults

Abstract: Background: Metabolic syndrome (MetS) in non-overweight/obese people is insidiously associated with cardiovascular disease (CVD). Novel anthropometric indices can reflect central obesity better than the traditional anthropometric indices. Therefore, we hypothesize that these newly developed anthropometric indices can better identify MetS in non-overweight/obese people than conventional indices. Methods: Cross-sectional data of sociodemographic, biochemical and anthropometric indices were collected from 2916 no… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…An increase in the prevalence of obesity has been reported in most Asian countries during the last two decades [29]. Several studies among different populations have shown that obesity-related indices can be used to predict MetS [11,13,14,30]. Xia et al demonstrated that LAP is a powerful marker of IR among people without diabetes [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the prevalence of obesity has been reported in most Asian countries during the last two decades [29]. Several studies among different populations have shown that obesity-related indices can be used to predict MetS [11,13,14,30]. Xia et al demonstrated that LAP is a powerful marker of IR among people without diabetes [31].…”
Section: Discussionmentioning
confidence: 99%
“…Anthropometric indices such as waist-to-height ratio (WHtR), waist-hip ratio (WHR), conicity index (CI), body mass index (BMI), body roundness index (BRI), body adiposity index (BAI), lipid accumulation product (LAP), abdominal volume index (ABSI), visceral adiposity index (VAI), abdominal volume index (AVI) and triglyceride-glucose index (TyG) can easily be calculated and quantified using factors such as triglycerides (TGs), body height (BH), hip circumference (HC), waist circumference (WC) and body weight (BW) [10]. These indices have been reported to be effective indicators of MetS in nonoverweight/obese adults, vegetarians and in Nigeria [11][12][13][14]. We recently identified associations between these obesity-related indices and nonalcoholic fatty liver disease and heavy metals [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The syndrome feeds into the spread of diseases such as type 2 diabetes, coronary diseases, stroke, and other disabilities. The total cost of the malady, including the cost of health care and loss of potential economic activity, is in the trillions [ 5 ].…”
Section: Introductionmentioning
confidence: 99%